A Compact CPW-Fed Low-Profile Wideband Circularly Polarized Slot Antenna with a Planar Ring Reflector for GNSS Applications - Jiade Yuan; Yujie Li; Zhimeng Xu; Jiamin Zheng (International Journal of Antennas and Propagation)
A compact low-profile wideband circularly polarized slot antenna for global navigation satellite system (GNSS) is presented. The antenna comprises a planar slot radiator with a coplanar waveguide (CPW) feed and a modified ring-shaped reflector to achieve unidirectional radiation. The modified reflector is an inner square patch with four slantly cut corners, a center ring, and an outer ring with a notch; they significantly reduce the separation between the antenna radiator and reflector and therefore the overall antenna height. The overall dimensions are λ0/3 × λ0/3 × λ0/30 (λ0 denotes the free space wavelength at lower frequency). The measured −10 dB bandwidth of |S11|, 3-dB axial ratio (AR) bandwidth, and maximum gain are of 1.53–2.28 GHz, 1.558–1.672 GHz, and 5.87 dBi, respectively. The proposed antenna is simple without any additional feeding networks or shorting probes.